Extensively drug-resistant tuberculosis case in the Thames Valley, UK and public health interventions - Muhammad Abid; Noel McCarthy; Luisa Saldaña; Tracey Langham; Anne McGown; Christopher Conlon; Pablo de Vena Franks (Elsevier, 2011)
Summary: This study describes the first case of extensively drug-resistant tuberculosis (XDR-TB) in the Thames Valley and South East Region and discuss the public health implications, highlighting the need to integrate current epidemiological knowledge with clinical expertise in order to diagnose drug-resistant tuberculosis (TB) early.The management of the XDR-TB patients is challenging with few treatment options, expensive therapy, side effects of drugs and a longer course of the treatment. Keywords: Extensively drug-resistant tuberculosis, Public health